2023
DOI: 10.3389/fonc.2023.1073891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the categorization method on the diagnostic performance of ultrasound risk stratification systems for thyroid nodules

Abstract: ObjectiveTo evaluate whether the categorization methods of risk stratification systems (RSSs) is a decisive factor that influenced the diagnostic performances and unnecessary FNA rates in order to choose optimal RSS for the management of thyroid nodules.MethodsFrom July 2013 to January 2019, 2667 patients with 3944 thyroid nodules had undergone pathological diagnosis after thyroidectomy and/or US-guided FNA. US categories were assigned according to the six RSSs. The diagnostic performances and unnecessary FNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…TIRADS appears to work well in tertiary/quaternary care units; however, it is less clear if it is applicable to primary/secondary care units [8,9]. Previous studies from our group have shown that in primary/secondary care units, the ttw shape of TNs is a frequent finding with a rate of 17%.…”
Section: Introductionmentioning
confidence: 79%
“…TIRADS appears to work well in tertiary/quaternary care units; however, it is less clear if it is applicable to primary/secondary care units [8,9]. Previous studies from our group have shown that in primary/secondary care units, the ttw shape of TNs is a frequent finding with a rate of 17%.…”
Section: Introductionmentioning
confidence: 79%